2pt=1qt
1pt=1/2qt
therefor
multiply 2 and 3/4 by 1/2
(2 and 3/4) times 1/2=(2+3/4) times 1/2=2 times 1/2+3/4 times 1/2=2/2+3/8=1+3/8=1 and 3/8 pt
Hope this helps. If you have any further question ask me in comment.
Step-by-step explanation:
(x+2y)(x-2y)
- x^2-2xy+2xy-(2y)^2
- x^2-4y^2
Answer:
1/2
Step-by-step explanation:
(1/16)^x
Let x = 1/4
(1/16)^ 1/4
Rewriting 16 as 2^4
(1/2^4)^ 1/4
We know that 1 / a^b = a^-b
(2 ^ -4)^ 1/4
We know that a^b^c = a^(b*c)
2^(-4*1/4)
2^-1
We know that a^-b = 1/ a^b
2^-1 = 1/2^1 = 1/2
Answer:
C. g(x) = 4x²
Step-by-step explanation:
The general equation for a parabola is
y = ax² + bx +c
Since ƒ(x) = x², a=1, b =0, c =0
For g(x), the vertex is still at the origin, so
g(x) = ax²
The graph passes through (1,4).
Insert the coordinates of the point.
4 = a(1)²
a = 4
g(x) = 4x²
The figure below shows that the graph of g(x) = 4x² passes through the point (1, 4).